Donor‐Derived Exosomes With Lung Self‐Antigens in Human Lung Allograft Rejection. Issue 2 (16th July 2016) - Gunasekaran, M.; Xu, Z.; Nayak, D. K.; Sharma, M.; Hachem, R.; Walia, R.; Bremner, R. M.; Smith, M. A.; Mohanakumar, T.
Abstract : The immunological role of exosomes in allograft rejection remains unknown. We sought to determine whether exosomes are induced during lung allograft rejection and to define the antigenic compositions of HLA, lung‐associated self‐antigens (SAgs) and microRNAs (miRNAs). Exosomes were isolated from sera and bronchoalveolar lavage fluid from 30 lung transplant recipients (LTxRs) who were stable or who had acute rejection (AR) or bronchiolitis obliterans syndrome (BOS). Exosomes were defined by flow cytometry for CD63 and western blotting for annexin V SAgs, collagen V (Col‐V) and Kα1 tubulin were examined by electron microscopy; miRNAs were profiled by a miRNA array. Donor HLA and SAgs were detected on exosomes from LTxRs with AR and BOS but not from stable LTxRs. Exosomes expressing Col‐V were isolated from sera from LTxRs 3 mo before AR and 6 mo before BOS diagnosis, suggesting that exosomes with SAgs may be a noninvasive rejection biomarker. Exosomes isolated from LTxRs with AR or BOS also contained immunoregulatory miRNAs. We concluded that exosomes expressing donor HLA, SAgs and immunoregulatory miRNAs are present in the circulation and local site after human lung transplantation and play an important role in the immune pathogenesis of acute allograft rejection and BOS. Abstract : Alloimmune responses induce exosomes with lung‐associated self‐antigens and regulatory microRNA, enabling the spread of immune responses that lead to lung allograft rejection.